2012
DOI: 10.1002/uog.12331
|View full text |Cite
|
Sign up to set email alerts
|

Fetal fraction in maternal plasma cell‐free DNA at 11–13 weeks' gestation: relation to maternal and fetal characteristics

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
323
5
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(367 citation statements)
references
References 24 publications
(52 reference statements)
20
323
5
11
Order By: Relevance
“…23 Prior studies have demonstrated that the fetal fraction is positively correlated with gestational age and negatively correlated with maternal weight. 24,25 These data suggest that NIPT may not be as effective in obese women or may need to be completed at later gestational ages.…”
Section: Discussionmentioning
confidence: 97%
“…23 Prior studies have demonstrated that the fetal fraction is positively correlated with gestational age and negatively correlated with maternal weight. 24,25 These data suggest that NIPT may not be as effective in obese women or may need to be completed at later gestational ages.…”
Section: Discussionmentioning
confidence: 97%
“…6,21,44 Data suggest that the lower limit of cell-free fetal DNA for a reliable result is approximately 4%. A no-call may be reported if there is not a sufficient amount of fetal cell-free DNA in the maternal blood sample.…”
Section: How Are No-calls Avoided Interpreted and Managed? Fetal Frmentioning
confidence: 99%
“…Fetal fraction decreased with increased maternal weight and was lower in women of Afro-Caribbean origin than Caucasians. Fetal fraction increased with fetal crown-rump length, serum pregnancy-associated plasma protein-A, serum free -human chorionic gonadotropin, smoking, and trisomy 21 karyotype (Ashoor et al, 2013). "Right now, there's not enough evidence to say one way or another whether the test should be used in average-risk women," Dr. Bianchi says.…”
Section: Looking Toward the Futurementioning
confidence: 99%